Body building on land: morphological evolution of land plants. - Dolan, L (2009)
Land plants are derived from green algal ancestors and made their first appearance on land 460 million years ago. The life cycle of the land plant body comprises two multicellular stages -- one haploid (gametophyte) and the other diploid (sporophyte). Recent discoveries suggest that the genes controlling diploid development in ancestral green algal zygotes diversified in the land plant lineage where they control the development of the diploid body plan. There are also numerous examples of the independent recruitment of sets of genes to control the development of structures that are morphologically and functionally similar. These discoveries are giving insights into the mechanism by which land plant morphologies changed over the past 460 million years.